2007
DOI: 10.1159/000107560
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Mindfulness in Psychotherapists in Training Influences the Treatment Results of Their Patients: A Randomized, Double-Blind, Controlled Study

Abstract: Background: All therapists direct their attention in some manner during psychotherapy. A special form of directing attention, ‘mindfulness’, is recommended. This study aimed to examine whether, and to what extent, promoting mindfulness in psychotherapists in training (PiT) influences the treatment results of their patients. Methods: The therapeutic course and treatment results of 124 inpatients, who were treated for 9 weeks by 18 PiTs, were compared. The PiTs were randomly assigned to 1 of 2 groups: (i) those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
164
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(185 citation statements)
references
References 39 publications
5
164
2
11
Order By: Relevance
“…The therapists were a mix of psychiatry residents, psychology interns, and licensed psychologists. In contrast to Grepmair et al 38 , there was not a significant relationship found between therapists' mindfulness and patient improvements assessed with the SCL-90. However, therapists' total mindfulness scores and scores on 'Accept without judgment' were significantly correlated with patient improvements in interpersonal functioning.…”
Section: Mindfulness In Clinical Practicecontrasting
confidence: 94%
See 1 more Smart Citation
“…The therapists were a mix of psychiatry residents, psychology interns, and licensed psychologists. In contrast to Grepmair et al 38 , there was not a significant relationship found between therapists' mindfulness and patient improvements assessed with the SCL-90. However, therapists' total mindfulness scores and scores on 'Accept without judgment' were significantly correlated with patient improvements in interpersonal functioning.…”
Section: Mindfulness In Clinical Practicecontrasting
confidence: 94%
“…While the literature is relatively sparse, in a critical review of the literature Escuriex and Labbé 29 reported that data from 20 studies were inconclusive with regard to whether clinicians' mindfulness or meditation practices had a positive impact on patients' outcomes. Yet, in a European clinical trial conducted by Grepmair et al 38 psychotherapists-in-training were randomized to a group taught Zen meditation (N=9 working with 63 inpatients) or not. The results indicated that the patients in the experimental group showed significantly better results e.g.…”
Section: Mindfulness In Clinical Practicementioning
confidence: 99%
“…Mindfulness on the part of mental health clinicians has been associated with significantly improved client outcomes compared to the clients whose clinicians do not meditate (Grepmair et al 2007). This suggests that the single, simple tool of provider mindfulness can have a powerful impact on client outcomes.…”
Section: The Attend Modelmentioning
confidence: 99%
“…61,62 Mindfulness interventions are possibly helpful for psychotherapists in treating their patients. 63 Mindfulness traits may also be a predictor of treatment outcome. 64 …”
Section: Pharmacotherapy/psychotherapymentioning
confidence: 99%